Sustainability evaluation of the Great Wall of China using fuzzy set concepts by incorporating Leadership Energy and Environmental Design. Issue 1 (2nd January 2017) - Yang, Jin; Tan, Fabian Hadipriono; Tan, Adrian; Parke, Michael
ABSTRACT: This paper discusses the sustainability performance of the ancient construction method and the service life during the Ming Dynasty on the Great Wall of China in Jinshanling. Jinshanling section of the Great Wall is located in Luanping County, approximately 150 km northeast of Beijing, China ["Beijing China to Jinshanling China." 2015. Google Maps, October 10. Accessed October 10, 2015]. To determine whether the Great Wall was sustainable during the time period, i.e. the Ming Dynasty, the authors use Leadership in Energy and Environmental Design guide and fuzzy set concepts (with the centroid method). The results of these methodologies demonstrate that the Great Wall of China in Jinshanling was fairly sustainable during the Ming Dynasty. After the conclusion of this paper, the authors hope to open up further research on whether the ancient construction methods from the Great Wall of China can be sustainable and used in today's construction industry.